The minor flagellin of Campylobacter jejuni (FlaB) confers defensive properties against bacteriophage infection - Lis, Lukas; Connerton, Ian F. (Frontiers Media, 2016)
A screen of bacteriophages infecting a panel of Campylobacter jejuni PT14 gene knock-out mutants identified a role for the minor flagellin encoded by the flaB gene, in the defense of the host against CP8unalikevirus bacteriophage CP_F1 infection. Inactivation of the flaB gene resulted in an increase in the susceptibility of PT14 cultures to infection by CP_F1 and an increase in bacteriophage yields. Infection of wild type PT14 with CP_F1 produces turbid plaques in bacterial lawns, from which 78% of the resistant isolates recovered exhibit either attenuation or complete loss of motility. CP_F1 produces clear plaques on the flaB mutant with no regrowth in the lysis zones. Complementation of the mutant restored overgrowth and the development of resistance at the expense of motility. Further analyses revealed an increase in bacteriophage adsorption constant of nearly two-fold and burst-size three-fold, relative to the wild type. Motility analysis showed no major reduction in swarming motility in the flaB mutant. Thus we propose a new role for FlaB in the defense of campylobacters against bacteriophage infection.